Chemical composition and antibacterial activity of coconut-shell liquid smoke to maintain the texture of fresh meat - Purwantisari, Susiana; Jannah, Siti Nur; Fikri, Dzakiyya Nabilla; Wulandari, Sukma Aulia; Yohana, Eflita; Setiyana, Budi; Ardiansari, Anindya; Amal, Daffa Ikhlasul; Ariyanto, Hermawan Dwi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
This research focused on the evaluation of raw broiler chicken meat texture and pathogenic antibacterial effect under the treatment of grade 2 coconut-shell liquid smoke (CSLS) as a food preservative. Compound identification of grade 2 CSLS was conducted using the GC-MS method. The main chemical compounds of CSLS were polyunsaturated fatty acid derivates, fatty acid and phenol. The evaluation of texture was conducted on raw broiler chicken meat under the treatment of grade 2 CSLS during storage at 25 ℃ for 7 days. The effect of antibacterial activity of grade 2 CSLS with different concentration (i.e., 5%, 25%, 50%, and 75%) were tested using Gram-positive bacteria on several pathogenic bacteria such as L. monocytogenes, S. aureus, P. Aeruginosa, and E. coli. The results indicated that grade 2 CSLS influenced the inhibited zone of L. monocytogenes, S. aureus, P. Aeruginosa, and E. coli respectively with linear correlation. The optimal concentration of grade 2 CSLS resulted in a concentration of 50%, which was the most optimal against L. monocytogenes, S. aureus, P. Aeruginosa, and E. coli as pathogenic bacteria strains.